Geo-Chicago 2016 : sustainable geoenvironmental systems : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (Geotechnical special publication ;, 2016)
Contains 99 peer-reviewed papers on landfill engineering and geosynthetics used for geoenvironmental systems. Topics include: design, testing, and evaluation of geosynthetics in geoenvironmental systems; landfill engineering; sustainable barrier materials and systems; vertical barriers for geoenvironmental applications; slopes, dikes, and embankments; ground improvement; and geoengineering of mine wastes and industrial byproducts.